2008
DOI: 10.1080/10903120701709878
|View full text |Cite
|
Sign up to set email alerts
|

Language Barriers as a Reported Cause of Prehospital Care Delay in Minnesota

Abstract: EMS responses troubled by delays in care secondary to language barriers represent a small percentage of total runs in Minnesota. However, approximately 1,370 cases per year occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
2
22
0
2
Order By: Relevance
“…Less is known about the communication between LEP callers and EMS. Research has demonstrated that EMS response times are longer for LEP callers [24]. Communication is particularly difficult at the point of first contact with the EMS operator/dispatcher when calling 9-1-1.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the communication between LEP callers and EMS. Research has demonstrated that EMS response times are longer for LEP callers [24]. Communication is particularly difficult at the point of first contact with the EMS operator/dispatcher when calling 9-1-1.…”
Section: Introductionmentioning
confidence: 99%
“…Grow et al reviewed prehospital encounters featuring a delay in the Minnesota State Ambulance Reporting System and found that language barriers were identified as the second most common cause of delay. 10 Intriguingly, however, the on-scene times for calls with a reported delay due to language barrier were actually shorter than the on-scene times for calls with no delay. A significant limitation of the study was that the “no delay” comparison group did not come from the general pool of all EMS encounters and it is unclear if these calls had atypical features that prompted EMS providers to specifically notate “no delay” in the report.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, the targets by which to evaluate quality of prehospital care in the context of language barriers do not appear to be well-defined. Is a shorter on-scene time for language discordant patients, as demonstrated in two studies, 10 , 32 advantageous or disadvantageous to patients? Prehospital medicine is riven by controversy regarding whether patient care is improved by shorter on-scene times as compared to more prolonged on-scene initiation of care.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have described the complexity of assessing an emergency call [ 3 , 6 , 7 ]. There are also studies identifying possible reasons for not identifying the caller’s need of care; language barriers [ 8 - 10 ] unnecessary questions asked by the EMD during the call [ 11 ], and lack of information from the caller [ 7 ]. Due to some of these difficulties, assessment protocols aiming to support the EMD’s assessment have been developed [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%